A Survey of Italian Radiation Oncologists: Job Satisfaction and Burnout. Issue 3 (May 2014) - Ruggieri, Valeria; Zeppegno, Patrizia; Gramaglia, Carla; Gili, Sabrina; Deantonio, Letizia; Krengli, Marco
Aims and Background: Job satisfaction and burnout can greatly affect the quality of life of professionals involved in the medical field and can also have an impact on many aspects of the work. The aim of the present study was to investigate professional history, professional satisfaction and burnout in Italian radiation oncologists. Methods and Study Design: Members of the Italian Association of Radiation Oncology (AIRO) were asked to complete a questionnaire composed of three sections including personal and professional information, the Job Satisfaction Scale (JSS) and the Link Burnout Questionnaire (LBQ). Results: The 167 participants were prevalently males working in public hospitals. About half of participants were staff physicians, mainly with no other specialty. Concerning the JSS, most respondents were moderately to extremely satisfied with their job. With regard to the LBQ, instead, we found critical results in the four investigated dimensions (psychophysical exhaustion, relation deterioration, professional failure and disillusion). Conclusions: This study suggests that Italian radiation oncologists have good medical background and education levels with a deep understanding of working in a clinical discipline. Organizational factors and the work climate are the main determinants of the satisfaction level and burnout is limited to a small percentage of professionals. The identification of specific profiles for professionals with higher levels of burnout or poorer job satisfaction may allow the delivery of targeted prevention or support interventions with the aim of improving workers' quality of life, satisfaction and perception of effectiveness.